Makna Menyendiri pada Individu Introvert di Masa Remaja dan Dewasa Awal - Putroe Habibul Ummi; Sri Nurhayati Selian (MASALIQ, 2026)
Although introverted personality has been widely examined in psychological research, studies that specifically discuss the subjective meaning of solitude among adolescents and young adults with introverted tendencies remain limited. Previous studies have tended to focus on patterns of social interaction, loneliness, and psychological well-being through quantitative approaches. This study aims to explore the meaning of solitude among individuals with introverted tendencies during adolescence and early adulthood. This study used a qualitative approach with a phenomenological design, involving three participants aged 18–20 years who were selected using purposive sampling. Data were collected through in-depth interviews and field notes, and were then analyzed using phenomenological analysis techniques. The results showed that solitude was interpreted as a positive psychological need because it functions as a means of self-reflection, emotional regulation, and energy recovery after social interaction. The experience of solitude was influenced by internal factors in the form of emotional fatigue and external factors in the form of unpleasant social experiences. However, excessive solitude has the potential to cause loneliness and a tendency toward overthinking. These findings contribute to the development of studies on personality psychology and psychological well-being by emphasizing that solitude can be understood as an adaptive strategy, rather than merely a form of maladaptive social withdrawal. The conclusion of this study emphasizes the importance of a balance between time spent in solitude and social interaction in maintaining the psychological well-being of individuals with introverted tendencies.